Developmentally regulated rat brain mRNAs: molecular and anatomical characterization - Miller, FD (J Neurosci, 1987)
In order to identify markers for developing neural cell populations and gain molecular insights into the processes of neural development and differentiation, we have selected cDNA clones of rat brain mRNAs that are expressed in brain at embryonic day 16 (E16) with at least 10-fold greater abundance than they are in adult brain. Eleven such clones were obtained from a cDNA library of E16 brain poly(A)+ RNA using a combination of differential and subtractive hybridization screens. The temporal and spatial patterns of expression of the mRNAs corresponding to these clones were characterized by Northern (RNA) blotting and by in situ hybridization. Although all the mRNAs were enriched in embryonic brain, different mRNAs demonstrated maximum abundance at different times in late embryogenesis. The mRNAs can be grouped into 3 classes on the basis of their patterns of spatial expression in the embryo: one cDNA clone from each class and its corresponding mRNAs have been characterized in more detail. Class C represents mRNAs that are highly enriched in the nervous system and may be expressed in newly differentiating neurons; the example chosen was shown by nucleotide sequence analysis to encode the brain alpha 1 isotype of tubulin. Class B mRNAs have a broader distribution in the developing embryo but are expressed predominantly in the ventricular germinal zones of the developing nervous system and may represent molecules involved with neurogenesis. A third class (Class A) includes mRNAs with a more homogeneous distribution within the embryo and developing nervous system, which may encode “housekeeping” molecules. These clones and their encoded products will provide markers for cell populations at particular stages of neural development.